Influence of wearing mouthguards on performance among athletes: A systematic review - Cao, R.; Zhang, X.; Xu, X.; Zhao, W.; Qiu, P.; Liu, W. (Journal of Science and Medicine in Sport, 2023)
Objectives While the use of mouthguards is well established to prevent orofacial and dental trauma occurrence, limited evidence exists regarding their influence on athletic performance. The objective of this study was to conduct a systematic review of the literature to assess the effect of wearing mouthguards on athletic performance.